ASESMEN AUTENTIK BERBASIS TEKNOLOGI DALAM PEMBELAJARAN BAHASA INDONESIA - Prasanty, Arum Berliana; Kuntoro, Kuntoro (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Learning evaluation in the Merdeka Curriculum positions authentic assessment as an essential component for assessing students’ competency achievement in a holistic and contextual manner. Along with the development of digital technology, the integration of technology into authentic assessment presents a strategic opportunity to enhance the quality of Indonesian language learning evaluation. This study aims to examine and analyze the concepts, benefits, and challenges of implementing technology-based authentic assessment in Indonesian language learning through a literature review. The research employed a qualitative descriptive method with a library research approach. Data were obtained through a systematic review of books, scientific journal articles, and relevant digital sources and were analyzed inductively to identify patterns and major themes. The results indicate that technology-based authentic assessment supports the authentic assessment of language competence through various digital literacy products, such as digital portfolios, multimedia projects, and online discussions. The integration of technology also accelerates feedback provision, enhances students’ learning motivation, and enables continuous, learner-centered evaluation. However, its implementation still faces challenges, including limited teacher competencies, infrastructure readiness, and variations in students’ digital literacy. This study concludes that technology-based authentic assessment has significant potential to improve the quality of Indonesian language learning evaluation in the Merdeka Curriculum, provided it is supported by strengthening teachers’ competencies and adequate technological infrastructure. ABSTRAK Evaluasi pembelajaran dalam Kurikulum Merdeka menempatkan asesmen autentik sebagai komponen esensial untuk menilai ketercapaian kompetensi peserta didik secara holistik dan kontekstual. Seiring perkembangan teknologi digital, integrasi teknologi dalam asesmen autentik menjadi peluang strategis untuk meningkatkan kualitas evaluasi pembelajaran Bahasa Indonesia. Penelitian ini bertujuan untuk mengkaji dan menganalisis konsep, manfaat, serta tantangan implementasi asesmen autentik berbasis teknologi dalam pembelajaran Bahasa Indonesia berdasarkan kajian literatur. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi kepustakaan (library research). Data diperoleh melalui penelaahan sistematis terhadap buku, artikel jurnal ilmiah, dan sumber digital yang relevan, kemudian dianalisis secara induktif untuk menemukan pola dan tema utama. Hasil kajian menunjukkan bahwa asesmen autentik berbasis teknologi mampu mendukung penilaian kompetensi berbahasa secara nyata melalui berbagai produk literasi digital, seperti portofolio digital, proyek multimedia, dan diskusi daring. Integrasi teknologi juga mempercepat pemberian umpan balik, meningkatkan motivasi belajar, serta memungkinkan evaluasi yang berkelanjutan dan berpusat pada peserta didik. Namun, implementasinya masih menghadapi tantangan berupa keterbatasan kompetensi guru, kesiapan infrastruktur, dan variasi literasi digital peserta didik. Simpulan penelitian ini menegaskan bahwa asesmen autentik berbasis teknologi berpotensi besar meningkatkan kualitas evaluasi pembelajaran Bahasa Indonesia dalam Kurikulum Merdeka, asalkan didukung oleh penguatan kompetensi guru dan penyediaan infrastruktur teknologi yang memadai.